2003
DOI: 10.1103/physrevlett.90.036601
|View full text |Cite
|
Sign up to set email alerts
|

Triplet-to-Singlet Exciton Formation in poly(p-phenylene-vinylene) Light-Emitting Diodes

Abstract: The triplet to singlet exciton formation ratio in a MEH-PPV light-emitting diode is measured by comparing the triplet-induced absorptions with optical and electric excitations at the same singlet exciton density. The ratio is a strong universal decreasing function of the averaged electric field. Using 4 ns for singlet to triplet intersystem crossing time, the ratio is significantly larger than the spin-independent value 3 at intermediate field but is reduced to about 2 for higher field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 15 publications
3
17
1
Order By: Relevance
“…Thus, the singlet generation yield is a true constant and, in contrast to previous reports [90,91], we find no electric field dependence with the drive voltages we have used. From these plots both el / el = 0.069 ± 0.002 and opt / opt = 0.0058 ± 0.0002 for electrical and optical excitations, respectively, and consequently the el/opt ratio can be obtained, 11.9 ± 0.8.…”
Section: Isrn Materials Sciencecontrasting
confidence: 53%
See 3 more Smart Citations
“…Thus, the singlet generation yield is a true constant and, in contrast to previous reports [90,91], we find no electric field dependence with the drive voltages we have used. From these plots both el / el = 0.069 ± 0.002 and opt / opt = 0.0058 ± 0.0002 for electrical and optical excitations, respectively, and consequently the el/opt ratio can be obtained, 11.9 ± 0.8.…”
Section: Isrn Materials Sciencecontrasting
confidence: 53%
“…Over the past few years, an increasing number of experimental reports make it clear that the 25% limit is broken [55][56][57][58][59]. In small-molecule-based OLEDs, original experimental evidence pointed to the 25% limit being obeyed [60,61], whereas in polymers this was not so; however, more recent reports, especially those from the OLED group in Kodak have shown that the 25% limit in small-molecule devices was also greatly exceeded [62,63].…”
Section: Exciton Formation In An Oledmentioning
confidence: 96%
See 2 more Smart Citations
“…This nonlinear loss mechanism for triplet excitons is in fact the reason why many previous studies drastically underestimated the number of triplet excitons generated, and thereby obtained excitation dependent (interpreted as electric fi eld-dependent) singlet exciton generation rates as high as 95%. 45,46 The results must therefore be studied and taken into account all together, in order to facilitate understanding.…”
Section: Annihilationmentioning
confidence: 99%